Virtual Reality effect on Mood changes in Cancer patients receiving chemotherapy treatment: a crossover trial - Ioannou, Androniki (Department of Nursing, Faculty of Health and Sciences, Cyprus University of Technology, 2021)
Background: Cancer patients are experiencing many chemotherapy-related symptoms which leads to negative mood changes. The development and application of modern technology in the health care field offers new and noninvasive approaches for cancer-related symptom management. Objective: To test whether Virtual Reality can benefit cancer patients from their interaction with an immersive environment experienced, on their mood state and their biophysical parameters, compared to those who will experience a Guided Imagery intervention. Methods: This was a randomized double blind, crossover trial with 50 cancer patients on active chemotherapy treatment, who randomized in a 1:1 allocation to one of two treatment sequences VR-GI or GI-VR. Patients were assessed for mood changes, some symptoms that can be affected from VR (Nausea, Pain, Feeling Sick) and bio-physical parameters (blood pressure, heart rate, oxygen saturation). Moreover, patients expressed their experience for VR intervention. Pearson r correlation, independent t-tests and Linear Mixed Effect Models were used for the statistical analysis. Results: Patients found to have a better effect of mood state after the VR intervention compared to GI, regardless of the sequence. Bio-physical parameters were statistically significantly improved after the use of VR. No changes appeared in the three symptoms of Nausea, Pain and Feeling sick. Participants found using VR during chemotherapy to be a very positive and incredible experience with good vibes and emotions. Conclusion: VR intervention based on mood induction strategies is an achievable procedure for promoting positive mood in cancer patients during their chemotherapy. Health care professionals should take into consideration these kinds of positive technologies.
Keywords: Virtual Reality; Mood; Mood changes; Chemotherapy-related symptoms; Cancer patients